P-CHAT OTC Trial (Humes et al., 2025) - Larry Humes (17028318) (2025)
Trial Design: This is a randomized multisite noninferiority comparative-effectiveness clinical trial with three parallel branches comparing a best-practices audiologist-fit method to two experimental self-fit (person-fit) methods. Outcomes were measured at 6 weeks and 6 months post-fit. Method: Participants: Five hundred eighty-four participants met the following inclusion criteria and enrolled: (a) age between 50 and 79 years; (b) never used or tried hearing aids previously; (c) can speak, read, and understand English well; (d) willing to purchase the study hearing aids for $650/pair; (e) no diagnosis of a memory or cognitive impairment; (f) 25-item Hearing Handicap Inventory for the Elderly (HHIE) score > 4; (g) Montreal Cognitive Assessment score ≥ 23; and (h) not excluded due to specific audiometric criteria. The audiometric exclusion criteria, based on air-conduction pure-tone thresholds, were as follows: (a) thresholds at all frequencies (250–8000 Hz) < 20 dB HL, for both ears (no hearing loss); (b) pure-tone average for 500, 1000, 2000, and 4000 Hz (PTA4) in the better ear > 50 dB HL (greater than moderate hearing loss); and (c) interaural difference > 20 dB at three or more frequencies or ≥ 40 dB at 500 or 1000 Hz. Interventions: Three groups received the same hearing aids fitted either by an audiologist using best practices (Group AB) or by themselves using one of two efficacious self-fit methods (Groups CD and EF). Objectives: The effectiveness of each of the self-fit methods, CD and EF, was hypothesized to be noninferior to the professional-fit method, AB. Outcomes: The primary outcome measure was the global score from the Profile of Hearing Aid Benefit (PHAB), and the secondary outcome measure was the benefit score (unaided – aided) for the 25-item HHIE. Randomization: Participants were stratified into one of three hearing loss categories based on better-ear PTA4: normal (≤ 20 dB HL), mild (20.1–35 dB HL), or moderate (35.1–50 dB HL). The random assignment of sequential enrollees within each hearing loss category to the three treatment groups made use of a site-specific pregenerated randomization list produced from a random-numbers table. Blinding: It was not possible to blind the participants as to the fitting method used, but the research personnel assessing the outcomes were blinded to the treatment group. Results: Numbers randomized: The 584 enrollees were randomized to one of the three treatment groups: AB (n = 190), CD (n = 193), and EF (n = 201).Trial status: The trial began on November 1, 2020, and 6-month outcomes were obtained from the last participant on March 29, 2024. Numbers analyzed: At the 6-week measurement interval, outcome measures were completed for 182 AB, 172 CD, and 178 EF participants, representing 91.1% of the 584 individuals who enrolled. At the 6-month interval, completed outcomes were available for 166 AB, 148 CD, and 151 participants, representing 79.6% of the 584 original enrollees. Outcome: Bootstrapped (N = 1,000) means and 95% confidence intervals (CIs) at 6 weeks were 16.4 (95% CI [14.3, 18.7]), 16.8 (95% CI [14.9, 18.6]), and 15.2 (95% CI [13.5, 17.1]) for the AB, CD, and EF treatment groups on the primary outcome measure (PHAB global). At 6 months, primary outcome scores were 15.5 (95% CI [13.4, 17.8]), 16.3 (95% CI [14.4, 18.2]), and 15.3 (95% CI [13.5, 17.3]) for the AB, CD, and EF treatment groups, respectively. At both measurement intervals, there were no significant effects of treatment group (p > .05) for the primary or secondary outcome measures. Harms: No significant adverse events or side effects were observed. Conclusions: At both the 6-week and 6-month postfit intervals, each of the two self-fit methods (CD, EF) yielded outcomes (primary and secondary) that were noninferior to the professional-fit best-practices (AB) fitting method. In addition, on average, clinically meaningful benefit was provided regardless of the fitting method. Supplemental Material S1. Outcome measures recorded at three sessions for each group separately presented for each site. Supplemental Material S2. Results from the physical and mental subscales of the PROMIS10 for sessions 1 and 3 separately presented for each site. Supplemental Material S3.Results of GLM analysis of outcome measures performed for separate hearing-loss subgroups. Humes, L., Dhar, S., Meskan, M., Pitman, A., & Singh, J. (2025). A multisite randomized controlled trial comparing the effectiveness of two self-fit methods to the best-practices method of hearing aid fitting. Journal of Speech, Language, and Hearing Research, 68(4), 2080–2103. https://doi.org/10.1044/2024_JSLHR-24-00423